2019
DOI: 10.1002/stem.2959
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Regulates P63 and Stem/Progenitor Cell State in the Corneal Epithelium

Abstract: Mutations in key transcription factors SOX2 and P63 were linked with developmental defects and postnatal abnormalities such as corneal opacification, neovascularization, and blindness. The latter phenotypes suggest that SOX2 and P63 may be involved in corneal epithelial regeneration. Although P63 has been shown to be a key regulator of limbal stem cells, the expression pattern and function of SOX2 in the adult cornea remained unclear. Here, we show that SOX2 regulates P63 to control corneal epithelial stem/pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…In vitro experiments: Human limbal rings from cadaveric corneas were obtained under the approval of the local ethical committee and declaration of Helsinki. Cells cultivation, differentiation, transfection, Western blot and real time polymerase chain reaction (qPCR) analyses were performed as previously described 101 . We used esiRNA against EGFP (EHUEGFP, Sigma), IFITM3 (EHU222801, Sigma) or GPHA2 (EHU036941, Sigma) and cells were collected 5-6 days after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro experiments: Human limbal rings from cadaveric corneas were obtained under the approval of the local ethical committee and declaration of Helsinki. Cells cultivation, differentiation, transfection, Western blot and real time polymerase chain reaction (qPCR) analyses were performed as previously described 101 . We used esiRNA against EGFP (EHUEGFP, Sigma), IFITM3 (EHU222801, Sigma) or GPHA2 (EHU036941, Sigma) and cells were collected 5-6 days after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Markers that allow purification of the clinically relevant cell material by sorting would significantly promote both the safety and efficacy of the future treatments [17]. However, this issue is complicated by the fact that a low level of pluripotency markers is also expressed in the primary human limbal epithelium [18], and some of these markers are critically involved in the regulation of stemness [19]. A thorough understanding of the LSC differentiation hierarchy and the functional roles of various LSC-related markers is required to be able to address these questions.…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study in 2015 by the same group found that miRs-103 and 107 enhances proliferation through different targets, including kinase p90RSK2, Wnt3a, NEDD9 (HEF1), and tyrosine phosphatase PTPRM 75 . On the other hand, miR-450b stimulates differentiation of limbal cells by repressing the SOX2/P63 pathway 80 .…”
Section: Mirnas and Corneal Epithelial Healing And Corneal Angiogenesis-mentioning
confidence: 99%